Perception of Dental Undergraduates and Interns towards E-Learning in Gaining Clinical Skills: A Cross-Sectional Survey - Vasiqa Bano; Ali Hassan Syed; Hashmat Gul; Nadia Mansoor (Life and Science)
Objective: To evaluate the level of acceptance of e-learning among dental interns and undergraduates of Armed Forces Institute of Dentistry (AFID). Study Design: Cross-sectional study. Place and Duration of Study: The study was carried out at Armed Forces Institute of Dentistry, Rawalpindi from March 2018 to September 2018. Materials and Methods: Cross-sectional quantitative survey was conducted in 174 participants   including dental interns and undergraduates. A fourteen-item questionnaire was designed and piloted. Data was tabulated and analyzed statistically using SPSS version 24.0. Categorical variables were presented as percentages. Post-stratification Fisher’s exact test and chi-square test were applied. p<0.05 was taken as significant. Results: Among clinical skills learning tools, more than half (54.6%) of the participants considered hospital attachments as most effective.  E-learning was considered a supportive tool for ward test preparation. Three quarters (75.3%) stated that e-learning has improved teaching standards and enhanced student-teacher interaction. There was significant association between level of education and messenger apps (p=.027), gender with accuracy in technique (p=.027) and with supervised discussion session regarding e-videos (p=.038). Conclusion: E-learning is beneficial for ward test preparation as it develops interest in clinical attachment and helps in learning general physical examination of patients.